2007
DOI: 10.1007/978-3-540-73614-1_2
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of Techniques to Detect Phishing Sites

Abstract: Abstract.Phishing is an electronic online identity theft in which the attackers use a combination of social engineering and web site spoofing techniques to trick a user into revealing confidential information. This information is typically used to make an illegal economic profit (e.g., by online banking transactions, purchase of goods using stolen credentials, etc.). Although simple, phishing attacks are remarkably effective. As a result, the numbers of successful phishing attacks have been continuously increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 5 publications
0
71
0
3
Order By: Relevance
“…Abu-Nimeh et al [9] adopted the bag-of-words strategy and used a list of words frequently found on phishing sites as features to detect phish, which is not expressive and easy to defeat by attackers. In [16], Ludl et al came up with a total of 18 properties solely based on the HTML and URL. The J48 decision tree algorithm was applied on these features and achieved a TP of 83.09% and a FP of 0.43% over a corpus with 4149 good pages and 680 phishing pages.…”
Section: Methods For Automatic Phish Detectionmentioning
confidence: 99%
“…Abu-Nimeh et al [9] adopted the bag-of-words strategy and used a list of words frequently found on phishing sites as features to detect phish, which is not expressive and easy to defeat by attackers. In [16], Ludl et al came up with a total of 18 properties solely based on the HTML and URL. The J48 decision tree algorithm was applied on these features and achieved a TP of 83.09% and a FP of 0.43% over a corpus with 4149 good pages and 680 phishing pages.…”
Section: Methods For Automatic Phish Detectionmentioning
confidence: 99%
“…Cybercriminals have also mitigated the efficacy of successful detections by churning through a large set of domains and URLs, with domain flux and URL fluxing [11,26,38,25]. Researchers, in turn, noting that this behavior is generally associated with malicious sites, have used it as a detection feature [20,31].…”
Section: Related Workmentioning
confidence: 99%
“…Several approaches have been proposed to detect phishing sites such as analyzing page content, layout, and other anomalies [22,26,31]. In addition, studies have analyzed the modus operandi of the criminal operations behind phishing [23], and the effectiveness of phishing defenses [25].…”
Section: Related Workmentioning
confidence: 99%